Efficacy and risks from a modified sodium nitrite toxic bait for wild pigs. Issue 4 (5th January 2021) - Snow, Nathan P; Wishart, Jason D; Foster, Justin A; Staples, Linton D; VerCauteren, Kurt C
Abstract: BACKGROUND: Wild pigs ( Sus scrofa ) are a destructive invasive species throughout many regions of the world. In 2018, a field evaluation of an early prototype of a sodium nitrite (SN) toxic bait in the United States revealed wild pigs dropped large amounts of the toxic bait outside the pig‐specific bait stations while feeding, and thus subsequent hazards for non‐target animals. We modified the SN‐toxic bait formulation, the design of the bait station, and the baiting strategy to reduce dropped bait. We tested the modifications in Queensland, Australia (December 2018), Alabama, USA (August 2019), and Texas, USA (March 2020) under differing climatic and seasonal conditions for one night. RESULTS: Cumulatively we found 161 carcasses of all age classes of wild pigs using systematic transects. Remote camera indices indicated high lethality for wild pigs, achieving population reductions of 76.3 to 90.4%. Wild pigs dropped only small particles of SN‐toxic bait (average = 55.5 g per bait site), which represented a 19‐fold decrease from the previous trial. Despite this reduction, we found three Australian ravens ( Corvus coronoides ) in Queensland, two Virginia opossums ( Didelphis virginiana ) in Alabama, and 35 granivorous‐passerine birds (mostly dark‐eyed juncos [ Junco hyemalis ]) in Texas dead from consuming the dropped bait. We did not detect any population‐level effects for those species. CONCLUSION: Our modifications were effective at reducing populations of wild pigs, but the deaths of non‐target species require further steps to minimize these hazards. Next steps will include evaluating various deterrent devices for birds the morning after SN‐toxic bait has been offered. Published 2020. This article is a U.S. Government work and is in the public domain in the USA Abstract : Modifications of a sodium nitrite toxic bait for wild pigs was evaluated to efficacy and non‐target risks. The bait quickly reduced populations of wild pigs, but non‐target deaths require further steps to mitigate risks in the USA. Published 2020. This article is a U.S. Government work and is in the public domain in the USA